Diagnosis of HLH: two siblings, two distinct genetic causes. (30th November 2021) - Escaron, Claire; Ralph, Elizabeth; Bibi, Shahnaz; Visser, Johannes; Aricò, Maurizio; Rao, Kanchan; Veys, Paul; Gilmour, Kimberly
Abstract: This report highlights case of two siblings who developed haemophagocytic lymphohystiocytosis due to distinct genetic abnormalities. Though their presentation was clinically similar, the cases demonstrate that a shared genetic diagnosis among siblings cannot be assumed. Abstract : This report highlights case of two siblings who developed haemophagocytic lymphohystiocytosis (HLH) due to distinct genetic abnormalities, in this case an X-linked condition (XLP1), and an autosomal recessive condition (FHL5). The cases demonstrate that suspicion of a primary immune deficiency (PID) must be investigated rapidly, and though their presentation was clinically similar, a shared genetic diagnosis among siblings cannot be assumed. Graphical Abstract: